Consumption Insurance, Welfare, and Optimal Progressive Taxation - Davud Rostam-Afschar; Jiaxiong Yao (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
Partial insurance of consumption against wage shocks is achieved through progressive taxation, labor supply adjustment, and precautionary wealth accumulation. The optimal degree of progressivity depends on preference and initial wealth conditions. More patient, more willing to work, and less wealthy households prefer more progressivity. The optimal progressivity is similar in Germany in comparison to the United States, though wealth has a greater impact on consumption insurance in Germany.
Keywords: D31; E21; H21; J22; 330